The Influence Of Financial Health On Bank Financial Performance - Aerlangga, Aerlangga (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the impact of bank financial health on financial performance using a quantitative method and multiple regression analysis. The research population consists of banks listed on the Indonesia Stock Exchange (IDX), while the sample is selected using the purposive sampling method, based on the availability of complete financial data. The independent variables used in this study are Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Non-Performing Loan (NPL), Operating Expenses to Operating Income (BOPO), and Net Interest Margin (NIM), with Return on Equity (ROE) as the dependent variable. The results indicate that NIM has a significant positive effect on ROE, while BOPO has a significant negative effect. Meanwhile, CAR, NPL, and LDR do not have a significant impact, suggesting that capital adequacy and credit risk are more related to long-term stability rather than profitability. The regression model explains 30.3% of ROE variability, with the remainder influenced by external factors. These findings emphasize that operational efficiency and optimal net interest margin management are crucial in improving bank profitability.